KEBIJAKAN HUKUM EKONOMI DALAM MERESPON PERKEMBANGAN LEMBAGA KEUANGAN MIKRO (MICRO FINANCE INSTITUTION) - Suyikno . (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2013)
Microfinance institutions (MFIs) has become an effective means to develop the economy and empower the people of the little people. The existence of MFIs is intended to meet the needs of capital and other financial services needs. It is therefore important to consider ways to encourage MFIs to develop better, especially in the context of economic empowerment and strengthening of the people's business. One of the serious problems encountered in economic development in Indonesia is practicing legal framework of economic policy in the development of economic policies. During this time, the issue is not important given the economic governance practices since independence has been running with the current logic of economic development that evolved on the basis of field experience or empirical theories and success stories in other countries are deemed worthy example. Hard to imagine that the constitution should diajdikan substantive reference in any official policy in the process of economic development. MFIs have grown long before the Republic was established. Especially the informal MFIs, grew roots with the development community. Since the days before independence, MFIs become an alternative for low-income group in meeting their funding needs. At that time, the MFI grows and develops in accordance with the variations required by society at that time without any intervention from the Government.